"Cherchez la fiction": Stories of Self-Realization in Anne Garréta's Pas un jour and Leïla Slimani's Sexe et mensonges. Issue 2 (1st July 2021) - BRUETON, JOANNE
Abstract : Faced with the hermetic interiority of post-structuralist narratives, twenty-first-century French literature tends to turn outwards and explore sociohistorical realities as a fertile source of fiction. In this article, I compare two contemporary writers rarely paired together—Anne Garréta and Leïla Slimani—to consider the enduring importance of discursive paradigms in realizing a sense of self. Although Garréta's mechanised autobiographical aesthetic in Pas un Jour seems to jar with Slimani's ethnographic journalism in Sexe et mensonges, I argue that both use heuristic narratives to conduct a survey of female desire whose reality is only legible in literature. Intersecting with narrative theories formulated by Barthes, Jameson and Cixous, this article argues that Slimani and Garréta perform their lived sexual experience through a carefully manufactured textual machine that grants them freedom. Only through the straitjacket of a fictional system can the reader glean the reality of female subjectivities so long obscured by myth.